Geographical location optimisation of wind and solar photovoltaic power capacity in South Africa using mean-variance portfolio theory and time series clustering - Joubert, Christiaan Johannes (Stellenbosch : Stellenbosch University, 2017)
Thesis (MEng)--Stellenbosch University, 2017.